Complete genome sequence and bioinformatics analyses of Bacillus thuringiensis strain BM-BT15426. (July 2017) - Liu, Junyan; Li, Lin; Peters, Brian M.; Li, Bing; Chen, Dingqiang; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Objectives: This study aimed to investigate the genetic characteristics of Bacillus thuringiensis strain BM-BT15426. Methods: B. thuringiensis strain was identified by sequencing the PCR product (amplifying 16S rRNA gene) using ABI Prism 377 DNA Sequencer. The genome was sequenced using PacBio RS II sequencers and assembled de novo using HGAP. Also, further genome annotation was performed. Results: The genome of B. thuringiensis strain BM-BT15426 has a length of 5, 246, 329 bp and contains 5409 predicted genes with an average G + C content of 35.40%. Three genes were involved in the "Infectious diseases: Amoebiasis" pathway. A total of 21 virulence factors and 9 antibiotic resistant genes were identified. Conclusions: The major pathogenic factors of B. thuringiensis strain BM-BT15426 were identified through complete genome sequencing and bioinformatics analyses which contributes to further study on pathogenic mechanism and phenotype of B. thuringiensis . Highlights: The genome of B. thuringiensis strain BM-BT15426 has a length of 5, 246, 329 bp and contains 5409 predicted genes. Three genes were involved in the "Infectious diseases: Amoebiasis" pathway. A total of 21 virulence factors and 9 antibiotic resistant genes were identified.